Radon concentrations and radiological risks in canned meats using etching technique - Alasadi Lubna; Raad Taher Mustafa; Baqer Mohammed Zahrah; Abojassim Ali Abid (BIO Web of Conferences)
This study evaluated the radon gas concentration of different samples of fresh canned meat available in Iraqi markets. A solid-state nuclear track detector (CR-39) uses a chemical etching technique for 1 hour at a temperature of 98°C in NaOH (6.25 N) concentrations. All radon, radium, and uranium concentrations were in an average value of 0.0461±0.0093Bq/kg 0.0041±0.00083 Bq/kg, and 0.0510±0.0103Bq/kg respectively. Also, radiological risks of annual effective doses were determined and found with Average values of 0.5066±0.1006 µSv/year, and also, excess live cancer risk was 1.773±0.3522. At the same time, all these values for infants, children, and adults were all within a safe limit. SPSS program version 26.0 showed descriptive statistics, histogram distribution and box plot, which shows that all values with normal distribution and some sample values were outliers. Finally, all values were within acceptable limits according to many international health organizations WHO, EPA, and ICRP and did not poss any hazard on human healt.